Apakah Manusia Purba Mampu Berbahasa Verbal? - Hari Suroto (Balai Bahasa Provinsi Papua, 2019)
Since Charles Darwin's theory of evolution is triggered, alot of speculation about the emergence of language. The data were found to date only limited fossil hominid skull, while the language itself does not fossilize. The data is the presence of artifacts of early human handiwork. Although the form of fossil skulls and artifacts, this data can be used to reconstruct the early emergence of language. Hominid fossils analyzed is representative for homo erectus skull found in Central Java Sangiran about 700,000 years old. Homo erectus fossil skull is the most complete Sangiran 17. Based on the analysis of the skull of Homo erectus Sangiran 17 is known that early man was able to speak, while the language is merely a proto-language.